2004
DOI: 10.1089/105072504323031013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iodine in Pregnant Women from the Boston, Massachusetts Area

Abstract: A DEQUATE MATERNAL IODINE intake is essential for fetal neurodevelopment. Worldwide, iodine deficiency is the leading cause of preventable mental retardation (1). Since the iodization of salt and other foods in the 1920s, U.S. dietary iodine has generally been adequate. However the median adult U.S. dietary iodine intake decreased by 50% from the time of the first National Health and Nutrition Examination Survey (NHANES I, 1971-1974) to the time of NHANES III (1988-1994) (2). Women of childbearing age may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 2 publications
0
29
0
1
Order By: Relevance
“…A limitation of the present study is that urine samples were not available for iodine measurements. However, we recently reported that low urinary iodine values (less than 50 μg/L) were present in 9 out of 100 pregnant Boston-area women sampled (31). Relatively few of the women in this study were taking multivitamins that contained iodine.…”
Section: Discussionmentioning
confidence: 54%
“…A limitation of the present study is that urine samples were not available for iodine measurements. However, we recently reported that low urinary iodine values (less than 50 μg/L) were present in 9 out of 100 pregnant Boston-area women sampled (31). Relatively few of the women in this study were taking multivitamins that contained iodine.…”
Section: Discussionmentioning
confidence: 54%
“…Based on UI evaluation, U.S. women of childbearing age may already be borderline iodine-deficient (23). Extensive data show that for U.S. women with UI <100 µg/L, perchlorate in urine, reflective of intake, was a significant negative predictor of thyroxine (p < 0.0001) and a positive predictor of TSH (p ) 0.001) (103).…”
Section: Iodine In Freshly Opened Containers Of Us Iodized Saltmentioning
confidence: 99%
“…In Poland, where iodization of household salt became obligatory in 1997, only 37% of the pregnant women had urinary iodine concentrations above 150 mg=L (27). Both a study performed in Boston, where 9% of pregnant women had urinary iodine concentrations below 50 mg=L (28), and a report of the National Health and Nutrition Examination Surveys (NHANES III) (29) have pointed out that urinary iodine is well below the values recommended by the World Health Organization and the International Council for Control of Iodine Deficiency Disorders (28)(29)(30). To prevent iodine deficiency, the American Thyroid Association (31) promoted iodine supplementation for pregnancy and lactation in the United States and Canada, recommending supplements of 150 mg iodine per day, this being the maximum permitted in nutritional supplements for pregnancy dispensed over-the-counter.…”
mentioning
confidence: 99%